Rethinking Scale in the Commons by Unsettling Old Assumptions and Asking New Scale Questions. Issue 1 (9th December 2020) - Smith, Hillary; Basurto, Xavier; Campbell, Lisa; Lozano, Alejandro Garcia
Scale is a powerful concept, a lens that shapes how we perceive problems and solutions in common-pool resource governance. Yet, scale is often treated as a relatively stable and settled concept in commons scholarship. This paper reviews the origins and evolution of scalar thinking in commons scholarship in contrast with theories of scale in human geography and political ecology that focus on scale as a relational, power-laden process. Beginning with early writings on scale and the commons, this paper traces the emergence of an explicit scalar epistemology that orders both spatial and conceptual relationships vertically, as hierarchically nested levels. This approach to scale underpins a shared conceptualization of common-pool resource systems but inevitably illuminates certain questions and relationships while simultaneously obscuring others. Drawing on critiques of commonplace assumptions about scale from geography, we reread this dominant scalar framework for its analytic limitations and unintended effects. Drawing on examples from small-scale fisheries governance throughout, we contrast what is made visible in the commons through the standard approach to scale against an alternative, process-based approach to scale. We offer a typology of distinct dimensions and interrelated moments that produce scale in the commons coupled with new empirical and reflexive scale questions to be explored. We argue that engaging with theoretical advances on the production of scale in scholarship on the commons can generate needed attention to power and long-standing blind spots, enlivening our understanding of the dynamically scaled nature of the commons.